(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to analyze the definition of «cohesion» and «coherence» in modern linguistics and describe their role in the text analysis, as well as correlate these terms with the notion of connectedness. We point out that the interpretation of these terms in various linguistic theories differs. However, having examined the research in the field of text coherence, we conclude that cohesion and coherence are the main categories of textual connectedness.